ANALYSIS OF SYNTHETIC ACCOUNTS USED IN SUBURBAN BUS TRANSPORT - Kilianova, Katarina (Doprava a spoje, 2012)
The main aim of the article is to analyse structure of synthetic and analytical accounts used in suburban bus transport services. The analysis should refer some differences in accounting in companies providing public passenger transport services. These differences can be base or pricing in public passenger transport or it can be the manner how to design economically justified costs.